2014
DOI: 10.1007/s11517-014-1174-6
|View full text |Cite
|
Sign up to set email alerts
|

Recurring patterns in stationary intervals of abdominal uterine electromyograms during gestation

Abstract: Abdominal uterine electromyograms (uEMG) studies have focused on uterine contractions to describe the evolution of uterine activity and preterm birth (PTB) prediction. Stationary, non-contracting uEMG has not been studied. The aim of the study was to investigate the recurring patterns in stationary uEMG, their relationship with gestation age and PTB, and PTB predictivity. A public database of 300 (38 PTB) three-channel (S1-S3) uEMG recordings of 30 min, collected between 22 and 35 weeks' gestation, was used. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…Statistically significant differences were obtained for sample entropy between term and preterm delivery records recorded before the 26 th GA and between all term and all preterm delivery records (Fele-Zorz et al, 2008). This result was consistent with the findings of other studies, which reported that sample entropy estimated from stationary motion and labor contraction-free intervals in EHG signals using the same database was lower for preterm delivery records than term delivery records (Di Marco et al, 2014). However, when sample entropy was computed for EHG-bursts from the same database, no statistically significant difference was found between preterm and term delivery records (Horoba et al, 2016).…”
Section: 1supporting
confidence: 90%
See 3 more Smart Citations
“…Statistically significant differences were obtained for sample entropy between term and preterm delivery records recorded before the 26 th GA and between all term and all preterm delivery records (Fele-Zorz et al, 2008). This result was consistent with the findings of other studies, which reported that sample entropy estimated from stationary motion and labor contraction-free intervals in EHG signals using the same database was lower for preterm delivery records than term delivery records (Di Marco et al, 2014). However, when sample entropy was computed for EHG-bursts from the same database, no statistically significant difference was found between preterm and term delivery records (Horoba et al, 2016).…”
Section: 1supporting
confidence: 90%
“…For patients with threatened preterm labor symptoms between 24 and 34 WG, a significant increase in approximate entropy computed in the bandwidth 0.24-4 Hz was found in patients who gave premature birth within 7 days, suggesting that the EHG signal becomes more complex as labor approaches (Lemancewicz et al, 2016). However, as the estimator of approximate entropy has been shown to be biased and highly sensitive to the number of signal samples (Ferrario et al, 2006), most authors prefer to use sample entropy, which is more independent of recording length and behaves more consistently, to characterize EHG signals (Fele-Zorz et al, 2008;Radomski et al, 2008;Garcia-Gonzalez et al, 2013;Di Marco et al, 2014;Horoba et al, 2016). Nevertheless, controversial results have been obtained for sample entropy estimated from EHG recordings.…”
Section: 1mentioning
confidence: 99%
See 2 more Smart Citations
“…In other words, as the time of gestation progresses, the MSampEn/MFSampEn values for both term and pre-term delivery records drop, indicating higher predictability or less complexity of the signals as the delivery approaches [43]. On the other hand, the MSampEn/MFSampEn values are lower for pre-term delivery records (middle-left, middle-right and bottom-right panel of Figure 5a,d,g) regardless of the gestation duration at the time of recording, which confirms that the preterm delivery records are less complex or more predictable than the signals of term delivery records.…”
Section: Feature Extraction Using Mmfe and Mmsementioning
confidence: 99%